Effects of dense planting pattern on the growth of apple tree in Weibei dry plateau - BAI Gangshuan; ZOU Chaoyu; DU Sheni; ZHENG Suolin; LIU Yingjun (浙江大学学报. 农业与生命科学版, 2019)
In order to improve the economic benefits of the apple orchard in Weibei dry plateau, taking the apple orchard with vigorous stock dense planting at the full bearing age as a control, the bearing fruit number of dwarfing stock dense planting and semi-dwarfing stock dense planting orchards were kept to the same with the vigorous stock dense planting orchard, and the tree growth status in different dense planting orchards with different stock-scion combinations was monitored. The results showed that the leaf area indexes of the dwarfing stock dense planting and semi-dwarfing stock dense planting orchards were 30.47% and 23.98% lower, and the leaf transpiration rates were 7.56% and 5.84% lower, but the leaf photosynthesis rates were 17.36% and 9.88% higher than that of the vigorous stock dense planting orchard, respectively. The tree growth in the dwarfing stock dense planting and semi-dwarfing stock dense planting orchards was smaller, but the fruit yields were basically consistent with that in the vigorous stock dense planting orchard. The fruit output value of the dwarfing stock dense planting and semi-dwarfing stock dense planting orchards increased by 8.58% and 7.43%, compared with that of the vigorous stock dense planting orchard, respectively. The above results indicate that the dwarfing stock dense planting and semi-dwarfing stock dense planting patterns can increase the production value of apple orchard, so the two dense planting patterns should be popularized in Weibei dry plateau.